Effect of Sunflower, Linseed and Soybean Meal in Pig Diet on Chemical Composition, Fatty Acid Profile of Meat and Backfat, and Its Oxidative Stability - Đorđević Vesna (Sciendo, 2016)
The aim of this study was to examine the effect of added sunflower, linseed or soybean meal to a standard pig fattening diet on the chemical composition, fatty acid profiles of meat and backfat, and on the oxidative stability of backfat from pigs. The content of saturated (SFA) and monounsaturated fatty acids (MUFA) was significantly lower (P<0.01), while content of polyunsaturated fatty acids (PUFA) was significantly higher (P<0.01) in the diet with added linseed. The feeding study was conducted on 30 pigs, with groups of 10 pigs fed one of the three different diets for 46 days before slaughter. There were no differences in the chemical composition (protein, water, fat, minerals) of meat from pigs fed the different diets. The content of SFA and MUFA was significantly higher, while the average PUFA content was significantly lower (P<0.01) in meat and backfat of pigs fed diet with added linseed. The content of n-6 fatty acids was significantly lower and n-3 fatty acids significantly higher, with more desirable n-6/n-3 ratio, in meat and backfat of pigs fed diet with added linseed. Malondialdehyde in the backfat of pigs fed diet with added linseed was significantly lower than that in the other two diet groups after the tissue was stored frozen at −20°C for 3, 6, 9 and 12 months.